KELONGGARAN PEMILIHAN DAN PENEMPATAN LEKSIKON SEBAGAI FITUR KESANTUNAN BERTUTUR MASYARAKAT JAWA PESISIR - M. Suryadi, M (Faculty of Humanities, Diponegoro University, 2015)
Politeness of Java coastal communities have a uniqueness when compared with the politeness of standard Javalanguage. Distinctiveness of its identity can beusedas a coastal community. Characteristic politeness Javanese coastal communities visible in the selection and placement of the lexiconon syntagmatic sequence. Selection of the lexicon is determined more by socio-cultural factors Javanese coastal communities. Placement of the lexicon is determined assuming more speakers than the alternation rules that apply in the standard Java language. The selection and placement of the lexicon in politeness Java coastal communities freed the standard Java language alternation rules.